Antibacterial Activities of Seaweed (Eucheuma cottonii ) Extract Against Escherichia coli Bacteria - Sukmawati, Sukmawati (Universitas Jember, 2021)
Indonesia is a maritime country that has more than 70% of its territory dominated by oceans and is a marine area that has abundant natural resources, one of which is Eucheuma cottonii. The content of compounds by E. cottonii has many benefits, the compound content of E.cottonii is a phenolic compound (flavonoids). Flavonoids found in seaweed E. cottonii are secondary metabolite compounds that can produce antibacterial activity. The purpose of this study was to determine the antibacterial activity of seaweed extract (E. cottonii) against Escherichia coli bacteria. The method that has been used in this research is descriptive method, including extraction, maceration, antibacterial activity test. The results of this study stated that the antibacterial activity of E. cottonii seaweed extract was able to inhibit the growth of E. coli bacteria. The highest antibacterial activity was found at a concentration of 50% ppm dry extract solution with a methanol solvent of 3.3 mm while the lowest antibacterial activity was found at a concentration of 5% ppm wet extract solution with a methanol solvent whose inhibitory activity value was 0.1 mm. Furthermore, the antibacterial activity test for positive control showed a strong inhibitory value of 7.8 mm, while the negative control did not indicate any inhibitory value against E. coli bacteria.